2017
DOI: 10.1073/pnas.1713168114
|View full text |Cite
|
Sign up to set email alerts
|

Strong attractions and repulsions mediated by monovalent salts

Abstract: Controlling interactions between proteins and nanoparticles in electrolyte solutions is crucial for advancing biological sciences and biotechnology. The assembly of charged nanoparticles (NPs) and proteins in aqueous solutions can be directed by modifying the salt concentration. High concentrations of monovalent salt can induce the solubilization or crystallization of NPs and proteins. By using a multiscale coarse-grained molecular dynamics approach, we show that, due to ionic correlations in the electrolyte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 67 publications
5
55
0
Order By: Relevance
“…The impact of salt concentration on the interaction potential between a pair of PAEs was studied by calculating the potential energies as a function of interparticle distance (i.e., core-to-core distance) ranging from 30 to 40 nm. Previous studies on nanoparticles with noncomplementary DNA strands exhibit repulsion forces between nanoparticles that are longer range than the repulsion predicted by DLVO theory when the salt concentration increases above 0.3 M, 25 which is in agreement with experiments on repulsion between charged surfaces at high monovalent salt concentrations. 26,27 This electrostatic interaction depends on multiple factors, including grafting density, temperature, and ionic strength, and can even lead to salting out.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The impact of salt concentration on the interaction potential between a pair of PAEs was studied by calculating the potential energies as a function of interparticle distance (i.e., core-to-core distance) ranging from 30 to 40 nm. Previous studies on nanoparticles with noncomplementary DNA strands exhibit repulsion forces between nanoparticles that are longer range than the repulsion predicted by DLVO theory when the salt concentration increases above 0.3 M, 25 which is in agreement with experiments on repulsion between charged surfaces at high monovalent salt concentrations. 26,27 This electrostatic interaction depends on multiple factors, including grafting density, temperature, and ionic strength, and can even lead to salting out.…”
Section: Resultssupporting
confidence: 87%
“…27 Furthermore, simulations have shown that the strength of interparticle interactions depends on the surface charge density of nanoparticles; at high salt concentration, weakly charged nanoparticles have a depletion-type attraction, whereas nanoparticles with moderate to high surface charge densities experience long-range repulsion attributed to ionic correlations. 25 In particular, for DNA-mediated colloidal assemblies, high salt concentration has been shown to induce phase transitions 28 and nanoparticle aggregation in the absence of hybridization interactions. 29 However, it is difficult with the current tools to gain a full understanding of the mechanism of how surface grafting densities and electrostatic energies cause salting out and affect crystal formation in systems with complementary linkers.…”
mentioning
confidence: 99%
“…Because DNA is negatively charged, increasing the amount of counterions in solution strongly modifies the interactions between individual PAEs and between PAEs and the substrate. These interactions have been shown to be more complex than simple charge screening [22][23][24] , meaning that fully understanding the complexity of this effect may require significant modeling of PAE assembly. However, prior work with the PAE design used here 20 has shown that at [NaCl] below 1.5 M, the combined result of these complex interactions resulted in increased surface coverage with increasing salt concentration.…”
Section: Textmentioning
confidence: 99%
“…The existence of multiple coexisting species-dependent decay lengths implies that addressable wetting could be achieved. Tuning the asymptotic correlations may also be used to control colloidal dispersions, for instance to prevent aggregation [6] and to switch effective potentials by tuning the salt concentration [45]. It might be promising to construct complex interactions to achieve a rich crossover structure, for instance in complex plasmas [46], colloid-polymer mixtures [47], and colloidal fluids [48].…”
Section: Which Is a Long Length Scale If Amentioning
confidence: 99%